A Highly‐Efficient KF‐Modified Nanorod Support Zr−Ce Oxide Catalyst and its Application. Issue 20 (20th September 2018) - Tang, Hongjuan; Li, Yongfei; Liu, Ning; Fu, Lin; Liu, Yuejin
Abstract: A novel KF‐modified nanorod support Zr−Ce oxide as an efficient solid base catalyst was prepared. XRD, FT‐IR, CO2 ‐TPD, TEM‐EDS, and Raman were employed for the catalyst characterization. The results showed that the appropriate activation temperature could facilitate the insertion of K + into the vacancy sites of the ZrO2 −CeO2 nanorod support, and some new strong basic active sites of K3 Zr2 F11, KCe2 F9, Ce2 Zr2 O7 were generated with the addition of KF on the mixed ZrO2 −CeO2 support. The prepared KF/ZrO2 −CeO2 as a solid base catalyst exhibited high activity and stability for transesterification of soybean oil with methanol to biodiesel. The high biodiesel yield of 99.8 % was obtained under the following conditions: 15 wt % KF loading amount, calcination temperature 400 °C, molar ratio of methanol/oil 20 : 1, 5 wt % catalyst account (wt/wt oil), reaction time 5 h at 65 °C. The formation of basic active sites of the KF/ZrO2 −CeO2 catalyst and the mechanism for the catalytic reaction were explored. Abstract : Turning beans to diesel : Nanorod support Zr−Ce is modified by base KF. Some new strong basic active sites of K3 Zr2 F11, KCe2 F9 and Ce2 Zr2 O7 were generated in the preparation process. The prepared KF/ZrO2 −CeO2 as a solid base catalyst exhibited high activity and stability for transesterification of soybean oil with methanol to biodiesel.